Potassium Nitrate Priming Effect on the Germination of Tomato (Lycopersicum esculentum. Mill) cvs. “Mersa” and “Tekeze-1” - Addisalem Mebratu (International Journal of Agronomy)
To compare the responses of two open-pollinated tomato varieties to germination parameters and shoot growth, seeds of open-pollinated tomato varieties, Mersa and Tekeze-1 were given osmopriming treatments with potassium nitrate (KNO3) in a lab setting. A completely randomized design with four replications was used. The analysis of variance revealed that both tomato varieties responded differently to priming with potassium nitrate concentrations significantly (P<0.05) for almost all measured traits. Potassium nitrate treatments also affected final germination percent (G%) and mean daily germination percent significantly (P<0.05) and germination index (GI) and shoot length (SL) (P<0.001). However, KNO3 did not have a significant effect on time for 50% germination (T50) and mean germination time (MGT). Variety Mersa showed better performance in germination percent (G%) and SL than Tekeze-1; while Tekeze-1 had shorter days for MGT and reached T50 faster than the Mersa variety. Potassium concentrations at 0.5% and 1.5% showed better germination results than the control and at 1% KNO3. The interaction of the Mersa variety with KNO3 at 1.5% and 1% resulted in the highest SL, but the Tekeze-1 variety had the highest shoot length at 0.5% KNO3 concentration, indicating that the varieties have different responses to the applied KNO3 rate. This study confirmed the possibility of enhancing seed germination through externally applied priming agents such as KNO3. Despite being a preliminary finding, this study demonstrated that tomato cultivars differ in how they react to KNO3 priming, and more research, using other tomato varieties and priming agents, is needed.